Exploring HIV prevention preferences among key populations in Uganda: A qualitative study - Maiya G. Block Ngaybe; Kawoya K. Joseph; Wadana Hamzazai; Carly J. Deal; Stephen Mugamba; Wambi M. Stephen; Richard Muhumuza; Betty Nakaggwa; Auwal Abubakar; Gabriela Valdez; Maia Ingram; John Ehiri; et al. (PLoS ONE, 2026)
Long-acting injectable pre-exposure prophylaxis (PrEP) has recently been approved for use, and dissemination, but has yet to be released in Uganda. To ensure uptake of this injectable option, and others like a future HIV vaccine, it is important to understand the preferences of the populations at the highest risk who will benefit the most. We present data on product preferences for HIV prevention practices and injectable HIV prevention among populations most at risk for HIV with a focus on injectable options such as long-acting PrEP or a future HIV Vaccine for primary prevention of HIV. From March 18–28, 2024, we conducted 20 semi-structured key informant interviews in English and Luganda among 10 experts in the field of HIV prevention, and 10 peer leaders of key or priority populations in Uganda. Participants were purposively selected to represent various groups, genders, occupations and locations to get diverse perspectives. Participants were included if they were determined to be at risk of contracting HIV and were above the age of 18. Both groups of participants were asked similar questions, with experts focusing on their experience with key populations, populations who are particularly vulnerable to HIV acquisition due to a combination of behavioral, biological, and social factors. Debriefs were held after each interview to monitor emerging themes and assess data saturation. The most common prevention practices mentioned by participants were condoms and PrEP. Participants mentioned barriers to prevention practices including duration (i.e., dosing length), accessibility issues such as transportation, location issues (i.e., distance), and stigma. The most important characteristics for participants when considering the uptake of a new injectable prevention product included efficacy, cost and side effects. Experts tended to believe that efficacy levels should be higher than peer leaders with lived experience. Participants who were peer leaders recognized that some had a fear of needles, though they also expressed motivation to receive injections due to the perception that they may work better than other modes of administration. According to experts and peer leader participants in this study, key populations in Uganda prefer high efficacy, lower side effects and confidentiality in their services. Participants emphasized the need for comprehensive and accessible information about specific HIV prevention methods to improve the uptake of these products. Tailored messaging and choice can accommodate the heterogeneity of preferences to best ensure HIV prevention in Uganda.